Stabilization of μ‐opioid receptor facilitates its cellular translocation and signaling. Issue 10 (12th June 2019) - Zhu, Cheng; Han, Qingjian; Samoshkin, Alexander; Convertino, Marino; Linton, Alexander; Faison, Edgar M.; Ji, Ru‐Rong; Diatchenko, Luda; Dokholyan, Nikolay V.
Abstract: The G protein‐coupled μ‐opioid receptor (μ‐OR) mediates the majority of analgesia effects for morphine and other pain relievers. Despite extensive studies of its structure and activation mechanisms, the inherently low maturation efficiency of μ‐OR represents a major hurdle to understanding its function. Here we computationally designed μ‐OR mutants with altered stability to probe the relationship between cell‐surface targeting, signal transduction, and agonist efficacy. The stabilizing mutation T315Y enhanced μ‐OR trafficking to the plasma membrane and significantly promoted the morphine‐mediated inhibition of downstream signaling. In contrast, the destabilizing mutation R165Y led to intracellular retention of μ‐OR and reduced the response to morphine stimulation. These findings suggest that μ‐OR stability is an important factor in regulating receptor signaling and provide a viable avenue to improve the efficacy of analgesics.